Near-surface dilution of trace Pd atoms to facilitate Pd-H bond cleavage for giant enhancement of electrocatalytic hydrogen evolution. (April 2017) - Li, Yaping; Chen, Shuangming; Long, Ran; Ju, Huanxin; Wang, Zhaowu; Yu, Xiaoxi; Gao, Fengyi; Cai, Zijian; Wang, Chengming; Xu, Qian; Jiang, Jun; Zhu, Junfa; et al.
Abstract: Pd is a versatile catalyst in various hydrogen-related catalytic applications; however, it typically exhibits low activity in electrocatalytic hydrogen evolution reaction (HER) as too strong Pd-H bonding makes the electronic desorption of H adatoms (Had ) hardly occur. We herein report a selective etching-deposition approach to implant trace Pd atoms in the near-surface region of Ag nanocrystals, forming a heteratomic-rich Pd-Ag structure on Ag surface. This near-surface dilution of Pd atoms can dramatically facilitate the electronic desorption of Had . As a result, this approach enhances the electrocatalytic HER activity of Pd catalysts about 14 times with excellent performance durability, approaching the high level of Pt catalysts. While enhancing the catalytic performance, this atomic implantation strategy allows the substantial reduction of material costs. This work thus represents a step toward the high-performance, low-cost catalyst design through near-surface lattice engineering. Graphical abstract: A selective etching-deposition approach has been developed to implant trace Pd atoms in the near-surface region of Ag nanocrystals. The formation of heteratomic-rich Pd-Ag structures can facilitate the electronic desorption of hydrogen adatoms to substantially enhance electrocatalytic hydrogen evolution reaction. Highlights: The near-surface dilution of trace Pd atoms is achieved to facilitate Pd-H bond cleavage. A selective etching-deposition approach is developed to isolate trace Pd atoms in the near-surface region of Ag nanocrystals. The electrocatalytic hydrogen evolution activity is improved about 14 times with excellent durability as compared with Pd catalysts. The surface lattice structure is unambiguously resolved by synchrotron-radiation characterizations. This work represents a novel strategy for high-performance and low-cost electrocatalyst design.